The myth of human races - Corcos, Alain F., 1925- (Michigan State University Press, 1997)
The idea that human races exist is a socially constructed myth that has no grounding in science. Regardless of skin, hair, or eye color, stature or physiognomy, we are all of one species. Nonetheless, scientists, social scientists, and pseudo-scientists have, for three centuries, tried vainly to prove that distinctive and separate ""races"" of humanity exist. These protagonists of race theory have based their flawed research on one or more of five specious assumptions: - humanity can be classified into groups using identifiable physical characteristics, - human characteristics a